10.1016/s0029-7437(07)70571-2 (CrossRef Listing of Deleted DOIs, 2000)
PURPOSE: To investigate the impact of intra/extracellular water exchange (WX) on quantitative dynamic contrast-enhanced (DCE) MRI in patients with severe aortic stenosis (AS). The aims were to compare low-dose (WX insensitive) and high-dose (WX sensitive) DCE-MRI measurements, and to compare data acquired before and after aortic valve replacement (AVR) to test whether DCE-MRI was able to detect changes in myocardial extracellular volume fraction (ECV). METHODS: Twenty-five patients with severe AS were studied at 3 T before and 6 months after AVR. DCE-MRI was performed at rest twice using a low contrast agent dose (0.05 mmol/kg gadobutrol) followed by a high-dose (0.1 mmol/kg gadobutrol). Estimates of myocardial blood flow (MBF) and ECV were obtained using models which assume instantaneous WX (fast exchange [FX]) and which incorporate WX (a two-site exchange [2SX] model). ECV estimates were also made using T1 maps acquired before and after contrast administration, both assuming FX and incorporating WX. RESULTS: FX model estimates of MBF and ECV obtained before AVR decreased from low- to high-dose contrast consistent with the effect of limited WX. This decrease was partially corrected using a 2SX model. However, 2SX model fits were preferred over FX fits in only 2 of 24 high-dose data sets (F-test). ECV estimates made using DCE-MRI increased after AVR consistent with changes seen using T1 maps, but the ECV estimates were lower. CONCLUSION: Estimates of MBF using DCE-MRI showed negligible sensitivity to WX. DCE-MRI-based ECV estimates changed post-AVR but were systematically lower than those made using T1 maps.